The Effects of Good Corporate Governance and Audit Quality on Earnings Management - Laily, Nujmatul (Journal of Accounting and Business Education, 2017)
A number of previous empirical studies have attempted to reveal the existence of earnings management. However, a research that focuses on how to alleviate the earnings management practices committed by managers is still insufficiently available. This study is aimed to examine the effects of Good Corporate Governance (GCG) and audit quality on earnings management. The presence of Board of Commisioner and Audit Commitee in Indonesian Manufacturing Public Listed Companies serves as the proxy of GCG. On the other hand, KAP (public accounting firm) size, dichotomous variables and an assumption that big four auditors perform higher audit quality compared to non-big four auditor serve as the proxy of the audit quality. To echo the prior research, earnings management is measured by employing discretionary accruals modified by Jone (1995). 151 manufacturing listed companies were determined as the population and 86 public listed companies were eventually opted for the sample. Purposive sampling method was employed and regression was performed to analyze the data. The results showed that (1) accounting firms size does not yield significant effects on earnings management. It indicates that neither big four nor non-big four can significantly detect the existence of earnings management undertaken by manager through the audit they administer; (2) Board of Commisioner and Audit Commitee also do not generate significant effects on earnings management. It indicates that good corporate governance proxied by the existence of Board Commisioner and Audit Commitee do not necessarily alleviate the earnings management practices.Â Keywords: Earnings management, audit quality, good corporate governance